This is not that kind of book - Healy, Christopher; Mantle, Ben (Random House, 2019)
"This clever alphabet book... Wait, that's not right. This original fairy tale... Nope. Mystery? Joke book? Superhero story? Pirate adventure? This delightful mash-up features every kind of character found in the picture-book universe--all in one book. Just when the reader is convinced the story is going in one direction, it spins off in another."--Amazon.
Keywords: Books -- Juvenile fiction; Friendship -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Picture books